Can the full range of paramedic skills improve survival from out of hospital cardiac arrests?. Issue 5 (September 1997) - Mitchell, R G; Guly, U M; Rainer, T H; Robertson, C E
Abstract : OBJECTIVE: To examine the effect of full implementation of advanced skills by ambulance personnel on the outcome from out of hospital cardiac arrest. SETTING: Patients with cardiac arrest treated at the accident and emergency department of the Royal Infirmary of Edinburgh. METHODS: All cardiorespiratory arrests occurring in the community were studied over a one year period. For patients arresting before the arrival of an ambulance crew, outcome of 92 patients treated by emergency medical technicians equipped with defibrillators was compared with that of 155 treated by paramedic crews. The proportions of patients whose arrest was witnessed by lay persons and those that had bystander cardiopulmonary resuscitation (CPR) were similar in both groups. RESULTS: There was no difference in the presenting rhythm between the two groups. Eight of the 92 patients (8.7%) treated by technicians survived to discharge compared with eight of 155 (5.2%) treated by paramedics (NS). Of those in ventricular fibrillation or pulseless ventricular tachycardia, eight of 43 (18.6%) in the technician group and seven of 80 (8.8%) in the paramedic group survived to hospital discharge (NS). For patients arresting in the presence of an ambulance crew, four of 13 patients treated by technicians compared with seven of 15 by paramedics survived to hospital discharge. Only two patients surviving to hospital discharge received drug treatment before the return of spontaneous circulation. CONCLUSIONS: No improvement in survival was demonstrated with more advanced prehospital care.